PENERAPAN ETNOPEDAGOGI DALAM PEMBELAJARAN BIOLOGI - Satriani Syam; Wawan Sujarwo (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2023)
An educator has an important role in building national and cultural identity, and ethnopedagogy can play an important role in this because it highlights local wisdom. Ethnopedagogy teaches problem-solving based on local wisdom, so that students' cognitive structures can be activated. This allows students to critically examine the problems that exist in their environment and produce original solutions that refer to the levels found in the local culture which serves as the basis. Critical and creative thinking skills can be instilled by combining problem-solving exercises based on local knowledge with the biology lessons. The method applied in this research is a literature study. The data used is a collection of articles in research journals available in the Google Scholar database and is devoted to learning in Indonesia. The selected literature consists of articles with qualitative and quantitative approaches. There are no limitations on publication year or language usage. The research results show that biology learning cannot be separated from its environment, and incorporating local wisdom in biology learning can make it a fun learning resource. Students can indirectly be trained to care about the surrounding environment, act as biological conservation agents, and preserve the values ​​contained in local wisdom. We conclude that the ethnopedagogical approach in biology learning can be applied because biology learning is natural science-based learning that can be linked to local wisdom. This application can also be expressed in learning media or tools to support the improvement of students’ interest.